2009
DOI: 10.3109/02713680903340746
|View full text |Cite
|
Sign up to set email alerts
|

Grading Contact Lens Complications: The Effect of Knowledge on Grading Accuracy

Abstract: 2Purpose: Grading contact lens complications is a time-effective process which, if performed accurately, may improve patient management significantly. Multiple factors have been identified that influence grading accuracy, such as the knowledge, training and experience of the observer. The aim of this study was to further explore the effect of knowledge on grading accuracy, both in terms of intensity and specificity, and to do so by avoiding the need to require the subjects to interpolate between whole number g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Subjective grading depends highly on the ability and accuracy of the clinician to make judgments about the condition in light of its severity and complexity [18]; when the observer has to grade two features (height and width), errors can occur while grading each of these aspects and in how they combine them, which can result in high variability. This limits the value in clinical studies due to factors such as the need for larger sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective grading depends highly on the ability and accuracy of the clinician to make judgments about the condition in light of its severity and complexity [18]; when the observer has to grade two features (height and width), errors can occur while grading each of these aspects and in how they combine them, which can result in high variability. This limits the value in clinical studies due to factors such as the need for larger sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the optometrist in charge of the subjective assessment was selected for his ample experience with the van Herick technique. Indeed, grading in general improves with training and with the experience and knowledge of the examiner . Besides, image capture and subjective grading were synchronous, once illumination, positioning and focusing conditions were considered optimal according to the van Herick description.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, grading in general improves with training and with the experience and knowledge of the examiner. 14,15 Besides, image capture and subjective grading were synchronous, once illumination, positioning and focusing conditions were considered optimal according to the van Herick description. Finally, although the aim of the study was to include patients with both open and narrow angles, the nature of our recruitment procedure, based on the consecutive selection of patients attending the University Vision Centre for routine optometric examination, produced a not unexpected larger percentage of eyes with open angles.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that this was probably due to their moderately trained observers before the commencement of the study. According to Cardona and Seres, 21 a change in grade of 0.5 units or greater made by experienced observers would represent a significant difference (because the 95% confidence limit is approximately twice the standard deviation). The present study also showed good intra‐observer agreement as shown by the high kappa value.…”
Section: Discussionmentioning
confidence: 99%